Síntese de novos adutos de morita-baylis-hillman entre o acrilato de 2-((7-cloroquinolin-4-il)oxi)etila e derivados de isatina com potencial atividade anticâncer - Mendes, Rhuan Karlos Santos (2021)
Cancer is the second leading cause of death worldwide. The methodologies used for cancer treatment have some problems such as high cost and high incidence of side effects, so the search for more effective drugs is always on the agenda in research groups. The use of molecular hybridization of privileged structures is a good alternative in the development of new drugs. Thus, this work aimed at the synthesis of four new molecular hybrids, derived from 2-((7-chloroquinolin-4-yl)oxy)ethyl acrylate and isatin derivatives, through the Morita-Baylis-Hillman reaction with potential anticancer activity, as well as to carry out a study in sílico of physical-compound properties in order to obtain data regarding the oral bioavailability of these compounds. The products were obtained with a variation of 65% to 75% in 40 h and were characterized by the technique of Nuclear Magnetic Resonance of carbon and hydrogen, NMR 13C and NMR 1H. Through the SwissADME online platform, tables and graphs were obtained showing the molecular hybrids as compounds that have good oral bioavailability and intermediates 2, 3 and 5 managed to permeate a blood-brain barrier. All compounds synthesized in this work will proceed to biological activity tests.